2008
DOI: 10.1007/s11101-008-9107-3
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modelling of aliphatic glucosinolate chain length distribution in Arabidopsis thaliana leaves

Abstract: Aliphatic glucosinolates are a major class of defensive secondary metabolites in plants that are mostly derived from methionine. Occurring in different chain lengths, they show a structural diversity arising from the variable number of chain elongation cycles taking place during their biosynthesis. The key enzymes in determining glucosinolate chain length are the methylthioalkylmalate (MAM) synthases, MAM1 and MAM3, with MAM3 showing a broader substrate specificity than MAM1. A comparison of the measurements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 42 publications
(61 reference statements)
1
14
0
Order By: Relevance
“…Another complex kinetic model in Arabidopsis simulates the synthesis of aliphatic glucosinolates (Knoke et al, 2009), which are important defensive metabolites in plants. The model compared the wild-type Arabidopsis leaves with knockout mutants of MAM1 and MAM3 (methylthiolalkylmalate).…”
Section: Examples Of Kinetic Models For Plant Metabolic Pathwaysmentioning
confidence: 99%
“…Another complex kinetic model in Arabidopsis simulates the synthesis of aliphatic glucosinolates (Knoke et al, 2009), which are important defensive metabolites in plants. The model compared the wild-type Arabidopsis leaves with knockout mutants of MAM1 and MAM3 (methylthiolalkylmalate).…”
Section: Examples Of Kinetic Models For Plant Metabolic Pathwaysmentioning
confidence: 99%
“…MAMa, MAMb and MAMc have originated by gene duplication events, and are functionally diversified. MAMa controls short-chain aliphatic glucosinolates (Benderoth et al 2006) and MAMb is, like its A. thaliana ortholog MAM3 Knoke et al 2008), presumably involved in the biosynthesis of long-chain aliphatic glucosinolates. However, the function of MAMc is not yet known.…”
Section: Generation Of Glucosinolate Diversitymentioning
confidence: 99%
“…MAM substrate specificity (Table 1) determines whether the reaction products of a given cycle enter the biosynthetic pathway generating the glucosinolate core structure or whether they undergo additional cycles of carbon chain elongation. A. thaliana MAM1 and MAM2 are involved in the formation of aliphatic glucosinolates with short carbon chains (Kroymann et al 2001;Textor et al 2004;Benderoth et al 2006), while MAM3 catalyzes condensation reactions in the biosynthesis of aliphatic glucosinolates with long carbon chains (Field et al 2004;Textor et al 2007; Knoke et al 2008). MAM synthases determine variability during the earliest stage of aliphatic glucosinolate biosynthesis and play a central role in glucosinolate diversity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in aliphatic glucosinolate synthesis, knockouts in one of several methylthioalkylmalate synthases generate varying patterns of glucosinolate chain lengths. Simulations using kinetic models revealed that chain length distribution is a function of the ratio, not of absolute activities, of different methylthioalkylmalate synthases (Knoke et al, 2009).…”
mentioning
confidence: 99%